THE POWER DEVIATION AS GROUNDS FOR NULLITY FOR ADMINISTRATIVE ACTS: CONCEPTUAL AND PROCEDURAL TREATMENT IN COLOMBIA, SPAIN AND PERU - Correa Zúñiga, César Luis (2023)
The nullity of administrative acts becomes a power held by the public administration either through a request by a party via a challenge or ex officio with the purpose of rendering administrative acts that contain a defect without effect as long as their rectification is not allowed or conservation. In the present case, the misuse of power in appearance becomes a lawful act, however, the issuing agent uses said appearance to satisfy either personal interests directly or indirectly, with which the administrative act ends up being a motive for the achievement of an ilegal purpose, using the position he holds, thus contravening the general interest. For this reason, it’s necessary to study its nature, conceptual and procedural treatment in order to determine if it allows its detection or, on the contrary, if other measures are required to warn of the production of actions that transgress the public purpose that comes with the issuance of administrative acts.